TEACHER READINESS IN RESPONSE TO EDUCATIONAL TRANSFORMATION: A Comprehensive Bibliometric Study - Thahir, Muthahharah; Tamam, Badrud; Gunawan, Irvan (Conciencia, 2024)
This study presents a bibliometric analysis of the scientific literature on "Teacher Readiness in Response to Educational Transformation," using the Scopus database to examine trends, collaborations, and key research themes. The analysis reveals a significant increase in publications since 2018, with a notable peak in 2021, likely due to the impact of the COVID-19 pandemic on education systems worldwide. Central themes include teacher readiness for integrating digital technologies, STEM education, and the challenges of online teaching. The keyword co-occurrence network highlights the close connections between teacher readiness and topics such as ICT, professional development, and early childhood education. Additionally, the country collaboration network shows strong contributions from the United States, Australia, China, and Hong Kong, although global cooperation remains limited. The study also identifies the most active journals, with the Australian Journal of Teacher Education and Journal of Research on Technology in Education being prominent platforms. The findings underscore the growing need for research on teacher preparedness to address the challenges of an evolving educational landscape. Future research should focus on emerging technologies like AI and VR in education, while expanding cross-country studies to ensure a more inclusive understanding of teacher readiness across diverse contexts.